A Unique Case of Midvariant Reverse Takotsubo Cardiomyopathy. (21st November 2018) - Moazez, Carmel; Zeitjian, Vicken; Mehdizadeh, Azar
Abstract : Takotsubo cardiomyopathy, also known as stress cardiomyopathy, is known to have 4 variants: apical, midventricular, basal, and focal. Here, we report the 2nd case of reverse midvariant (midventricular) stress cardiomyopathy and the 1st case of reverse midvariant takotsubo cardiomyopathy with apical thrombus.